EFFECT OF COMPENSATION, WORK FACILITY, SAFETY AND OCCUPATIONAL HEALTH ON THE SATISFACTION OF HARVEST MANDOR (SURVEY IN PT. PERKEBUNAN NUSANTARA V SEI.GALUH, SEI.GARO AND TANDUN) - Fitri Hidayanti; Arman Arman; Yulizar Baharuddin (STIE Bangkinang Publishing, 2020)
This study aims to determine the effect of compensation, work facilities, safety and health on the job satisfaction of the harvest foreman at PT. Perkebunan Nusantara V Sei. Galuh, Sei. Garo and Tandun. The samples in this study were all harvest foremen at PT. Perkebunan Nusantara V Sei. Galuh, Sei Garo and Tandun, totaling 30 harvest foremen. The data collection techniques used were questionnaires and research files. The data analysis technique used is multiple linear regression analysis with a significant level (α) of 0.05. Simultaneously compensation, work facilities, occupational safety and health have an effect on job satisfaction, based on the partial test results compensation and work facilities have an effect on job satisfaction, while occupational safety and health have no effect on job satisfaction of the harvest foreman. The closeness of the relationship of the independent variable to the dependent variable is very strong with the contribution of the independent variable to the fixed variable which is 90,6%.